2021
DOI: 10.1302/2046-3758.1012.bjr-2021-0288.r2
|View full text |Cite
|
Sign up to set email alerts
|

3D printing in orthopaedic surgery: a scoping review of randomized controlled trials

Abstract: Aims The use of 3D printing has become increasingly popular and has been widely used in orthopaedic surgery. There has been a trend towards an increasing number of publications in this field, but existing literature incorporates limited high-quality studies, and there is a lack of reports on outcomes. The aim of this study was to perform a scoping review with Level I evidence on the application and effectiveness of 3D printing. Methods A literature search was performed in PubMed, Embase, and Web of Science dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…A recent systematic review demonstrated that 3D printing technology in orthopedics improves operative time, blood loss, fluoroscopy times, bone union time, pain, accuracy, function, and without an increase in operative complications[ 12 ]. Besides being used for preoperative planning, surgery simulation, intraoperative navigation, patient education, and doctor-patient communication, 3D-printing technology has shown emerging and promising application in personalized spinal implant and reconstructive surgery[ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review demonstrated that 3D printing technology in orthopedics improves operative time, blood loss, fluoroscopy times, bone union time, pain, accuracy, function, and without an increase in operative complications[ 12 ]. Besides being used for preoperative planning, surgery simulation, intraoperative navigation, patient education, and doctor-patient communication, 3D-printing technology has shown emerging and promising application in personalized spinal implant and reconstructive surgery[ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] With the application of 3D-printing, we are now able to fabricate prostheses in any shape. 27,28 As the elbow joint is a complex articulation that could hardly be abstracted into a simple mechanical model, 3D-printing technique could produce a metal 'humerus' or 'ulna' with the same articular surface as that of the original bone, fulfilling the purpose of bionic reconstruction. In this paper, we share the preliminary results of elbow hemiarthroplasty in 13 patients who underwent reconstruction with a 3D-printed distal humeral or proximal ulnar megaprosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The global 3D-printing market is growing in the field of orthopedics and spine surgery [ 1 , 2 , 3 ]. Companies and surgeons are increasingly adopting 3D printing for custom or patient-specific implants [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Companies and surgeons are increasingly adopting 3D printing for custom or patient-specific implants [ 4 , 5 , 6 , 7 , 8 ]. 3D printing is also becoming ever more popular for surgical planning [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] as well as for educational purposes.…”
Section: Introductionmentioning
confidence: 99%